Long-term prognosis after endoscopic submucosal dissection for colorectal tumors in patients aged over 80 years - Tomoyuki Nishimura (BMC Gastroenterology, 2021)
Abstract Background In Japan, endoscopic submucosal dissection (ESD) is standardized for large colorectal tumors. However, its validity in the elderly population is unclear. We aimed to evaluate the safety and efficacy of ESD for colorectal tumors in elderly patients aged over 80 years. Methods ESD was performed on 178 tumors in 165 consecutive patients aged over 80 years between December 2008 and December 2018. We retrospectively evaluated the clinicopathological characteristics and clinical outcomes of ESD. We also assessed the prognosis of 160 patients followed up for more than 12 months. Results The mean patient age was 83.7 ± 3.1 years. The number of patients with comorbidities was 100 (62.5%). Among all patients, 106 (64.2%) were categorized as class 1 or 2 according to the American Society of Anesthesiologists classification of physical status (ASA-PS), and 59 (35.8%) were classified as class 3. The mean procedure time was 97.7 ± 79.3 min. The rate of histological en bloc resection was 93.8% (167/178). Delayed bleeding in 11 cases (6.2%) and perforation in 7 cases (3.9%) were treated conservatively. The 5-year survival rate was 89.9%. No deaths from primary disease (mean follow-up time: 35.3 ± 27.5 months) were observed. Overall survival rates were significantly lower in the non-curative resection group that did not undergo additional surgery than in the curative resection group (P = 0.0152) and non-curative group that underwent additional surgery (P = 0.0259). Overall survival rates were higher for ASA-PS class 1 or 2 patients than class 3 patients (P = 0.0105). Metachronous tumors (> 5 mm) developed in 9.4% of patients. Conclusions ESD for colorectal tumors in patients aged over 80 years is safe. Colorectal cancer-associated deaths were prevented although comorbidities pose a high risk of poor prognosis.